The Development of Play Therapy Model Based on Karonese Culture for Child Victims - Sudirman, Sudirman; Handayani, Silvia Mariah; Susanti, Sani (Journal of Nonformal Education, 2018)
This study aims to develop a play therapy model based on Karonese Culture to reduce the trauma of children after the eruption of Mount Sinabung. The approach in this study used a qualitative approach during preliminary study, design and model formulation. Quantitative approaches will be used when testing and validating models. The method used is 4D model: Define, Design, Develop and Disseminate. Under the trend category, the mean of child trauma is 111.00 and lies at intervals of 96 to 128. This suggests that child trauma belongs to high category. Based on the observation of Sinabung children, it is known that many of them are traumatized. The trauma to these children can be identified with some symptoms. Three things to note from the direct changes experienced by these children, namely: (1) Avoidance: avoid what is associated with the incidence of eruption; (2) Re-experiencing: traumatic events continue to reoccur in memory so that children often experience bad dreams; (3) Hypersoul: a visible trauma reaction. Children are often frightened when they hear the sound of explosions and loud shouts. Another sign is the emergence of regression in children where there is a decline in their development. Furthermore, children who are usually active tend to withdraw themselves from the environment, and conversely, a quiet child becomes active. Based on the findings, the instructional games will be designed with the stages of application design starting with the concept, designing, collecting materials, assembly, testing and distribution.